Bukhari's Kitāb Tafsir al-Qur'an - Melchert, C (International Qur'anic Studies Association, 2017)
The celebrated Ṣaḥīḥ (full title: Al-Jāmiʿ al-musnad al-ṣaḥīḥ al-mukhtaṣar, meaning roughly “the comprehensive, fully supported, sound epitome”) of Abū ʿAbd Allāh Muḥammad b. Ismāʿīl al-Bukhārī (d. 256/870) is divided into ninety-seven chapters, of which the second largest is kitāb tafsīr al-Qurʾān (“the book of qurʾānic commentary”). It constitutes about 7 percent of the whole work. Marston Speight has a useful discussion of it in a 1988 article, recently revisited by Aisha Geissinger, but I should like to go further by way of measuring the extent of Bukhārī’s reliance on Companions and other later authorities in comparison with his reliance on the Prophet; otherwise comparing this book with the rest of the Ṣaḥīḥ; and comparing this book with other notable collections of ḥadīth.1 It confirms Bukhārī’s unusual attention to adab (belles-lettres), more pronounced than ever in this book. It seems a valuable witness to the state of qurʾānic commentary in the mid-ninth century, a time from which we have few others.